Exploring land use scenarios by long-term simulation of soil organic matter in central Argentina - Tittonell, P.A.=700 1 De Grazia, J.; De Hek, S.; Bricchi, E.
(Es, En)
ilus., 27 ref.
Keywords: CONSERVACION DE SUELOS; MEJORA DE LA TIERRA; EXPLOTACION AGRICOLA INTENSIVA; SIMULACION; INVESTIGACION OPERATIVA; MATERIA ORGANICA; ROTACION DE CULTIVOS; CALIDAD; SUELO; ESPAÑA